Controlling Mold Growth in the Home - Bode, Marilyn; Munson, Deanna (My University, 1995)
This publication contains information about mold and how to get rid of it in the home.
MF2141_1995_09
Keywords: MF2141; Health and Safety; Home and Family; MF